Strategic Competency Development for Frontliners to Strengthen Customer Loyalty: A Study in General Insurance Services at PT XYZ - Ayu Indriani Martawilaga; Dedy Sushandoyo (Eduvest - Journal of Universal Studies, 2026)
The general insurance market in Indonesia remains growing and competition is shifting towards the service excellence side with diminishing product differentiation. As for PT XYZ, the frontline employees are the tip of the spear in determining how the customer feels about the company. Consider the performance of the companys Customer Loyalty Index CLI between 2020–2024 it is below the target and those of competitors suggesting the firm faces challenges sustaining loyalty. Customer feedback indicates satisfaction is associated with frontline capability when interacting during service provision. The purpose of this study is to measure the competency of the frontline at PT XYZ, to analyze the gap of competency from which lead to loyalty, and to recommend the strategy for improvement. Using the Knowledge–Skills–Attitudes (KSA) framework, this study identifies four critical competencies which directly impact customer loyalty (1) customer knowledge (2) problem-solving ability (3) adaptability ability and (4) Empathy Attitude. Taking a mixed-methods approach that combines competency assessments with expert interviews, the results indicate that current capability levels for these four competencies remain well below human-expected thresholds. Not enough understanding of the customer leads to less personalization, bad problem resolution leads to slower service resolution, low adaptability leads to disrupted responsiveness in the face of a system or policy changes, and weak empathy leads to diminished emotional connection with the customer. We propose a competency improvement plan based onfocused development programs in customer insight and modeling, sensitive exposure to customer behavior, discipline in practical problem-solving, and customer empathy-oriented service approach reinforcement.